THE INTEGRATIVE ROLE OF FINANCIAL LITERACY, FINANCIAL TECHNOLOGY, AND DIGITAL ACCOUNTING ON MSME PERFORMANCE: A LITERATURE REVIEW - Sev Rahmiyanti; Agung Praptapa; Puji Lestari; Eliada Herwiyanti (ZILLZELL MEDIA PRIMA, 2026)
This study aims to comprehensively analyze the integrative role of financial literacy, financial technology, and digital accounting on the performance of micro, small, and medium enterprises (MSMEs) through a literature review approach. The method used was a qualitative-descriptive literature review by analyzing 30 SCOPUS-indexed international journal articles (Q1, Q2, and Q3) that were relevant to the research topic. The analysis process is carried out through data extraction, thematic grouping, and narrative synthesis to identify patterns of relationships between variables. The results of the study show that financial literacy plays a role as a foundation in financial decision-making and management, financial technology functions as an enabler in improving the efficiency and access to financial services, and digital accounting contributes to improving the quality of financial information and decision-making. These three variables interact with each other and form integrative relationships in influencing the performance of MSMEs. The conclusion of this study confirms that the integrative approach between financial literacy, financial technology, and digital accounting provides a more comprehensive understanding in explaining the performance of MSMEs compared to the partial approach. This research contributes to the development of literature related to MSMEs in the digital era and becomes the basis for further research.